Studies on the Relative Merits of Popular Commercial Orchid Hybrids and Their Clonal Derivatives - Ibrahim, Noraini (1983)
Two orchid hybrids, Aranda Chris tine and Aranda Kooi Choo with seven clone seach, were studied with respect to the variations of morphological characters of their flowers prays. The shelf life of cut flowers and production of flowers were also investi gated. Highly significant differences occurred between clones of Aranda Christine. The length of spray was positively correlated with the length of scape, length of rachis, flower internodes and the average horizontal measurements. Clone numbers 80 and 130 had long. sprays while clone number 05 had the shortest. Clone swith long scapes tended to have long rachis and long flower internodes. Thelong rachis normally had larger flowers resulting in a negative correlation with the shelf life. The highest producer was clone number I but analysis did not show superior result sin all the parameters observed. The clones of Aranda Kooi Choo showed highly significant differences between them. The long sprays tended to have long rachis and larger flowers. Thus the flowers prays of Aranda Kooi Choo were stiff and strong. Clones with large f lowers were clone" numbers 2, 4 and 5 with clone number 2 also having the widest diameter of scape. Clone number 3 had the smallest flowers. Length of flower inter node and shelf life were not correlated to any o f the parameters studied. Clone number I has the longest shelf life but the re were no significant difference among other clones. Clone numbers 3 and 7 were high producing with clone number 2 as the lowest producer.